2020
DOI: 10.1017/s0022029920000527
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal contact on activity, emotionality and social competence in young dairy calves

Abstract: The study reported in this research communication aimed to assess the influence of maternal contact on calves' activity, fearfulness, and social competence. Calves were either dam-reared for their first 14 d of age (Maternal Contact, n = 12) or were separated from their dams within 12 h after birth (Motherless, n = 12). Calves of both treatments and the dams of Maternal Contact calves were group-housed and suckling was prevented with udder nets. The general activity (lying, locomotion, swapping between lying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Results from the behavioural tests indicate that type of CCC or debonding strategy did not affect calves' level of fearfulness. This finding is in line with previous studies that also reported no differences in fearfulness between calves reared without CCC or with full CCC during an OFT and NOT at 14 days of age (Santo et al, 2020) or 65 days of age (Buchli et al, 2017). Individual calves differed substantially in their behaviour responses during the different behavioural tests, which is in agreement with other studies that reported large individual differences in fearfulness that were stable over time, related to personality and sociality traits (Lecorps et al, 2018;van Reenen et al, 2005van Reenen et al, , 2004, and were linked to mood-states (Lecorps et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Results from the behavioural tests indicate that type of CCC or debonding strategy did not affect calves' level of fearfulness. This finding is in line with previous studies that also reported no differences in fearfulness between calves reared without CCC or with full CCC during an OFT and NOT at 14 days of age (Santo et al, 2020) or 65 days of age (Buchli et al, 2017). Individual calves differed substantially in their behaviour responses during the different behavioural tests, which is in agreement with other studies that reported large individual differences in fearfulness that were stable over time, related to personality and sociality traits (Lecorps et al, 2018;van Reenen et al, 2005van Reenen et al, , 2004, and were linked to mood-states (Lecorps et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…This 4 weeks timeframe was repeated throughout the experiment 8 times (to 8 veal farms). The exact age at transport was (mean ± SEM [range]): 2 weeks transport = 19.5 ± 0.3 (16)(17)(18)(19)(20)(21)(22) days; 4 weeks transport = 33.1 ± 0.4 (30)(31)(32)(33)(34)(35)(36) days.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…cross sucking) 14 , (2) increases in certain diseases, such as calf diarrhoea 15 and dam mastitis 16,17 , and (3) lower weight gain of the calf 15 . Early dam-calf separation has moreover been linked to poorer social skills and reduced sociability (as a personality trait) in the calves [18][19][20][21] and later when they become adult 22,23 . Compared to dam-reared calves, calves separated shortly after birth show lower levels of specific social behaviours, including social play, submissive behaviours and agonistic behaviours 14 .…”
mentioning
confidence: 99%
“…Nevertheless, new CCC systems should accommodate particular behaviours that cattle are motivated to perform, such as allogrooming and suckling. Cow−calf pairs housed in a free-suckling system spend between 10 and 60 min per 24 h on each of the behaviours suckling and allogrooming the calf (Lidfors, 1996; Paranhos da Costa et al ., 2006) and it is evident that maternal contact influences the emotional development of the calf (Santo et al ., 2020) and, in the short term only, their response to human contact (Waiblinger et al ., 2020). Further, cows and calves respond vocally to separation, and high-pitched vocalizations can be used as an indicator of stress at separation (Johnsen et al ., 2015).…”
mentioning
confidence: 99%